2017
DOI: 10.20849/aes.v2i4.283
|View full text |Cite
|
Sign up to set email alerts
|

EFL Pre-Service Teachers’ Perceptions of CLIL

Abstract: This study aims to investigate EFL pre-service teachers' perceptions of CLIL concerning what CLIL is, what CLIL provides, what CLIL requires, who should implement CLIL, and where CLIL teachers should be trained. The participants were EFL pre-service teachers studying in the faculty of education, Mahasarakham University, Thailand. Questionnaires were used to collect the data after the introduction of CLIL. The findings revealed that most of the participants knew the notion of CLIL as they had taken the teacher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Our findings highlight that these preservice teachers noted that implementing CLIL in the school requires large amounts of lesson planning and teaching time, as it involves a particular language focus. Teachers spend a long time choosing the appropriate content, designing activities, and adapting and preparing materials (Tachaiyaphum & Sukying, 2017). Therefore, all participants agreed that CLIL is not easy to implement as it is time-consuming (Mehisto et al, 2008) and requires much effort from the teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlight that these preservice teachers noted that implementing CLIL in the school requires large amounts of lesson planning and teaching time, as it involves a particular language focus. Teachers spend a long time choosing the appropriate content, designing activities, and adapting and preparing materials (Tachaiyaphum & Sukying, 2017). Therefore, all participants agreed that CLIL is not easy to implement as it is time-consuming (Mehisto et al, 2008) and requires much effort from the teachers.…”
Section: Discussionmentioning
confidence: 99%
“…This exploratory, descriptive study was carried out using a questionnaire. Since we did not find previous work addressing this particular issue, the questionnaire was elaborated, taking as a reference the interview guide of Arizmendi Tejeda et al (2016), the questionnaire of Tachaiyaphum and Sukying (2017), and our own questions. In addition, it was subjected to expert judgment, after which some questions were included, and others were removed or redefined.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Therefore, there are some important differences when researchers observe students in class. At first, they were confused and elemental when the researcher asked them for vocabulary (Tachaiyaphum & Sukying, 2017;Taslim et al, 2019). They are usually silent and afraid to mention the vocabulary themselves.…”
Section: The Implementation Of Tpr To Teach Vocabulary In Sdn Karanga...mentioning
confidence: 99%
“…Some previous studies about the implementation of CLIL had been conducted by McDougald (2015), Syzdykbayeva (2017), Tachaiyaphum andSukying (2017), andCampillo et al (2019). According to several previous studies, numerous researchers are exploring the teachers' perception of CLIL implementation.…”
Section: Introductionmentioning
confidence: 99%
“…According to several previous studies, numerous researchers are exploring the teachers' perception of CLIL implementation. The analysis indicated that the CLIL was helpful for teachers (Johnson, 2012;Puspitasari, 2016;Tachaiyaphum and Sukying, 2017;McDougald, 2015) because it could benefit the students in learning content and language. However, there is a limited study examining students' perception of CLIL implementation in the classroom.…”
Section: Introductionmentioning
confidence: 99%